Regulation of Peripheral Nerve Myelin Maintenance by Gene Repression through Polycomb Repressive Complex 2 - Ma, Ki H. (J Neurosci, 2015)
Myelination of peripheral nerves by Schwann cells requires coordinate regulation of gene repression as well as gene activation. Several chromatin remodeling pathways critical for peripheral nerve myelination have been identified, but the functions of histone methylation in the peripheral nerve have not been elucidated. To determine the role of histone H3 Lys27 methylation, we have generated mice with a Schwann cell-specific knock-out of Eed, which is an essential subunit of the polycomb repressive complex 2 (PRC2) that catalyzes methylation of histone H3 Lys27. Analysis of this mutant revealed no significant effects on early postnatal development of myelin. However, its loss eventually causes progressive hypermyelination of small-diameter axons and apparent fragmentation of Remak bundles. These data identify the PRC2 complex as an epigenomic modulator of mature myelin thickness, which is associated with changes in Akt phosphorylation. Interestingly, we found that Eed inactivation causes derepression of several genes, e.g., Sonic hedgehog (Shh) and Insulin-like growth factor-binding protein 2 (Igfbp2), that become activated after nerve injury, but without activation of a primary regulator of the injury program, c-Jun. Analysis of the activated genes in cultured Schwann cells showed that Igfbp2 regulates Akt activation. Our results identify an epigenomic pathway required for establishing thickness of mature myelin and repressing genes that respond to nerve injury.